2022
DOI: 10.3390/jcm11113234
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Carotid In-Stent Restenosis by Computed Tomography Angiography Carotid Plaque-Based Radiomics

Abstract: In-stent restenosis (ISR) after carotid artery stenting (CAS) critically influences long-term CAS benefits and safety. The study was aimed at screening preoperative ISR-predictive features and developing predictive models. Thus, we retrospectively analyzed clinical and imaging data of 221 patients who underwent pre-CAS carotid computed tomography angiography (CTA) and whose digital subtraction angiography data for verifying ISR presence were available. Carotid plaque characteristics determined using CTA were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For predictive power, the mean AUC of the final models in training group was 0.876±0.09, ranging from 0.741 to 0.989. Internal validation was performed in 14 studies ( 25 - 27 , 29 , 32 - 38 , 40 , 41 , 43 ), and 1 study employed external validation ( 42 ), but only 12 studies ( 25 , 26 , 29 , 32 - 34 , 36 - 38 , 40 , 41 , 43 ) reported the AUCs of the validation groups, ranging from 0.73 to 0.986. Model calibration was investigated in 7 studies (36.8%) and demonstrated good calibration performance ( 25 , 30 , 32 , 37 , 40 , 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For predictive power, the mean AUC of the final models in training group was 0.876±0.09, ranging from 0.741 to 0.989. Internal validation was performed in 14 studies ( 25 - 27 , 29 , 32 - 38 , 40 , 41 , 43 ), and 1 study employed external validation ( 42 ), but only 12 studies ( 25 , 26 , 29 , 32 - 34 , 36 - 38 , 40 , 41 , 43 ) reported the AUCs of the validation groups, ranging from 0.73 to 0.986. Model calibration was investigated in 7 studies (36.8%) and demonstrated good calibration performance ( 25 , 30 , 32 , 37 , 40 , 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Through radiomics or texture analysis, 10 studies tended to classify unstable or risk plaques ( 25 , 27 , 29 , 32 , 33 , 39 - 43 ). Moreover, 5 studies focused on predicting unfavorable cerebral and cardiovascular events ( 28 , 35 - 38 ), 2 on evaluating stenosis or in-stent restenosis ( 26 , 30 ), 1 on assessing the robustness of radiomics features ( 34 ), and 1 on evaluating the relationship between glycated hemoglobin and ultrasound plaque textures ( 31 ). The details are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations